ORGANIZATIONAL COMMUNICATIONS ON THE MEANING OF A CRITICAL APPROACH TO FEMINISTIC THEORY - Oktri Permata Lani; Muhammad Husni Shidqi; Ilham Havifi; Miftahurrahmi Fitri (State Institute of Islamic Studies Batusangkar, 2021)
A critical theory of communication (or economics, or politics) needs to involve a critique of society as a whole. Critical communication theory deals with a variety of relevant topics, including language, organizational structure, interpersonal relations, and the media. Communication itself according to a critical perspective is a result of the pressure (tension) between individual creativity in providing a framework for messages and social constraints. Development in the millennium era The Millennium Development Goals (MDG's) have one of the goals of which is towards the equal partnership of men and women by increasing justice and gender equality in every development sector. However, the problem of gender inequality is indicated by the low quality of life and the role of women, the high number of acts of violence against women as measured by the Gender-related Development Index (GDI) and the Gender Empowerment Index (GEM). The research method used is qualitative in a literature review approach